Enhancing academic resilience through culturally integrated cognitive behavioral therapy and expressive writing: a study of batak university students - Siregar, Ilham Khairi; Degeng, I Nyoman Sudana; Atmoko, Adi; Ramli, M. (Psikopedagogia, 2025)
This study aims to determine the effectiveness of integrating Batak cultural values into Cognitive Behavioral Therapy (CBT) incorporating expressive writing to enhance academic resilience among university students. Using a single-subject A-B-A experimental design, the research involved five final-year students, measuring changes in academic resilience before, during, and after the intervention. The culturally infused CBT sessions integrated key Batak values such as kekerabatan (kinship), hamajuon (perseverance), and hasangapon (honor) alongside expressive writing exercises. Results showed a significant improvement in academic resilience, emotional regulation, adaptive help-seeking behaviors, and cultural identity reinforcement. These findings underscore the importance of culturally relevant therapeutic interventions in fostering academic resilience. Based on these results, it is recommended that future studies explore the long-term impact of such interventions and assess their effectiveness among diverse cultural groups to enhance their broader applicability in educational and psychological settings.